Incorporation of Aegilops biuncialis chromosomes into wheat and their identification using fluorescent in situ hybridization - Schneider, Annamária; Molnár, István; Molnár-Láng, Márta (Acta Biologica Szegediensis, 2008)
The aim of the study was to select Aegilops biuncialis chromosomes from the progeny of the BC2 and BC3 generations of the wheat xAe. biuncialis hybrids, which differ from the chromosomes 2M, 3M, 7M, 3U and 5U found in the wheat-Ae. biuncails addition lines produced earlier in Martonvásár. Besides the above mentioned addition lines exists a 5U, 6U double disomic addition line. Chromosomes of the progeny of the BC2 and BC3 generations and the 5U, 6U double disomic addition line were counted with Feulgen method, while alien (Ae. biuncialis) chromosomes were identified with fluorescent in situ hybridization (FISH) using pSc119.2 and AFA family DNA probes. During the present experiment it was found that the transmission percentage of the chromosome 5U is 67,55% in the progeny of the BC2 and BC3 generations, while in the 5U, 6U disomic addition line chromosome 5U showed 100% transmission. Besides the chromosomes incorporated in the wheat-Ae. biuncialis addition lines produced in Martonvásár, some plants containing the chromosomes 1U, 2U, 4U, 6U, 7U, 5M and 6M without the presence of the chromosome 5U exist. These plants are potential sources of the production of new wheat-Ae. biuncialis addition lines.